2022
DOI: 10.1177/09589287221091687
|View full text |Cite
|
Sign up to set email alerts
|

Learning losses and educational inequalities in Europe: Mapping the potential consequences of the COVID-19 crisis

Abstract: It is widely discussed that the pandemic has impacted educational inequalities across the world. However, in contrast to data on health or unemployment, data on education outcomes are not timely. Hence, we have extremely limited knowledge about pandemic-related learning losses at the national and cross-national levels. As it might take years to get suitable comparative data, this study uses the latest large-scale international achievement survey from before the pandemic, the Trends in International Mathematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…For instance, several studies (see, for example, Engzell et al, 2021 ; Hevia et al, 2022 ) showed that Covid-19 had a detrimental effect especially on the achievement of students from less advantaged backgrounds. During school closures, these students are less likely to have had access to a computer, an internet connection, and a space conducive to learning ( Blaskó et al, 2022 ; Di Pietro et al, 2020 ). Moreover, as argued by Ariyo et al (2022) , one would expect children of less educated parents to have received less parental support while learning at home than children of more educated parents.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, several studies (see, for example, Engzell et al, 2021 ; Hevia et al, 2022 ) showed that Covid-19 had a detrimental effect especially on the achievement of students from less advantaged backgrounds. During school closures, these students are less likely to have had access to a computer, an internet connection, and a space conducive to learning ( Blaskó et al, 2022 ; Di Pietro et al, 2020 ). Moreover, as argued by Ariyo et al (2022) , one would expect children of less educated parents to have received less parental support while learning at home than children of more educated parents.…”
Section: Resultsmentioning
confidence: 99%
“…The shift to remote learning during the COVID-19 pandemic has brought about several new challenges that have affected students, teachers, and parents. These challenges may include but not limited to: access to Internet and technologies for remote learning (Lockee, 2021 ; Mbhiza, 2021 ), difficulties in learning engagement (Salas-Pilco, 2022 , Tamah et al, 2020 ), inequities in education (Blaskó, 2022 ; Walters, 2020 ), increased academic anxiety (Hong, 2021 ; Kamran & Naeim, 2021 ; Rashid, 2022 ), mental health (Maqsood, 2021 ; Zhai & Du, 2020 ), and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, more than 90% of the children worldwide were affected by temporary school closures during the pandemic (UNESCO, 2022). Although it is still unclear how the suspension of face-to-face teaching in schools impacted children's academic skills and achievement in detail, research raises serious concerns about its social, economic, and public health consequences for society (Kuhfeld et al, 2020;Lee, 2020;Engzell et al, 2021;Psacharopoulos et al, 2021;Raw et al, 2021;Waite et al, 2021;Blaskó et al, 2022;Ravens-Sieberer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%